Automation and Monitoring of Hydroponic Cultivation with Solar Panel Optimization Integrated Internet of Things - Abdullah; Putri, Maharani; Rusdi, Muhammad; Cholish (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
Limited land is one of the problems in plant cultivation. Hydroponic cultivation is a solution to this problem. This research aims to develop an automation and monitoring system for hydroponic cultivation that utilizes energy from solar panels and is integrated with the Internet of Things (IoT). This system is designed to increase the efficiency of energy use and simplify the monitoring and management of hydroponic plants. Solar panels are used as the main energy source to support the operation of IoT devices and automation systems, including water pumping and lighting. Through IoT integration, data related to environmental conditions such as temperature, humidity, and light intensity can be accessed in real-time through a web-based application. System tests show that this technology is able to provide accurate data and improve energy efficiency, as well as assist farmers in monitoring and managing crops more effectively. The results of this research show the potential of using IoT technology and renewable energy in modern agriculture, especially in hydroponic cultivation systems.